‘Double Displacement Reaction’ is a Misnomer in Chemistry - Parashar, Renu; Parashar, R. K. (SCHOOL SCIENCE, 2018)
The introductory science curriculum deals with physical and chemical changes. Under the chemical changes, various chemical changes/ reaction types, including single displacement and double displacement, are discussed separately. However, on keen observation and analysis, one can conclude that both types can be termed as simply displacement/replacement reactions